2022
DOI: 10.3389/fpls.2022.1074106
|View full text |Cite
|
Sign up to set email alerts
|

Genetic background- and environment-independent QTL and candidate gene identification of appearance quality in three MAGIC populations of rice

Abstract: Many QTL have been identified for grain appearance quality by linkage analysis (LA) in bi-parental mapping populations and by genome-wide association study (GWAS) in natural populations in rice. However, few of the well characterized genes/QTL have been successfully applied in molecular rice breeding due to genetic background (GB) and environment effects on QTL expression and deficiency of favorable alleles. In this study, GWAS and LA were performed to identify QTL for five grain appearance quality-related tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…GWAS depend on the association between molecular markers and the phenotype of the target trait. The combined analysis of QTL mapping and GWAS can improve the accuracy of QTL/gene detection and has been used in rice ( Famoso et al., 2011 ; Zhai et al., 2018 ; Pan et al., 2020 ; Chen et al., 2022 ) and maize ( Wang et al., 2019 ; Li Z. et al., 2020 ). However, in wheat, few studies using this combination analysis have been reported ( Chen et al., 2016 ), and the following genes were detected: TaFLL-5B1 for flag leaf length ( Yan et al., 2020 ), qHR-1B for herbicide resistance ( Shi et al., 2020 ), and S2B_26494801 for drought tolerance of winter wheat ( Sallam et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…GWAS depend on the association between molecular markers and the phenotype of the target trait. The combined analysis of QTL mapping and GWAS can improve the accuracy of QTL/gene detection and has been used in rice ( Famoso et al., 2011 ; Zhai et al., 2018 ; Pan et al., 2020 ; Chen et al., 2022 ) and maize ( Wang et al., 2019 ; Li Z. et al., 2020 ). However, in wheat, few studies using this combination analysis have been reported ( Chen et al., 2016 ), and the following genes were detected: TaFLL-5B1 for flag leaf length ( Yan et al., 2020 ), qHR-1B for herbicide resistance ( Shi et al., 2020 ), and S2B_26494801 for drought tolerance of winter wheat ( Sallam et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, even fewer well characterized genes/QTL have been successfully used in breeding for enhancing grain yield. The main reasons are that the QTL mapping results largely depend on the genetic background and no QTL have been simultaneously detected in completely different genetic backgrounds in the multi-parent advanced generation inter-cross (MAGIC) populations research [15]. The QTL are mapped in populations that generally differ from breeding populations and cannot be detectable in the breeding population, thereby limiting their application in molecular breeding.…”
Section: Introductionmentioning
confidence: 99%
“…The QTL are mapped in populations that generally differ from breeding populations and cannot be detectable in the breeding population, thereby limiting their application in molecular breeding. Although association mapping using diversity maize panels can identify favorable alleles, it is difficult to directly use them in breeding due to the poor performance of accessions in terms of many important agronomic traits [15]. Therefore, to identify background-independent QTL, integrating QTL mapping with molecular breeding in the same population will largely minimize the effect of genetic background on QTL detection [15].…”
Section: Introductionmentioning
confidence: 99%